2009
DOI: 10.1007/s00127-009-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese version of the strengths and difficulties questionnaire in Hong Kong

Abstract: Our data support the use of the Chinese version of the SDQ, especially the total difficulties scale, as a screening instrument for psychiatric morbidities among children in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 15 publications
11
103
0
Order By: Relevance
“…35 The Strengths and Difficulties Questionnaire is a local validated questionnaire assessing 5 aspects of adolescent life, including emotional problems, conduct problems, peer relationships, hyperactivity/ inattention, and prosocial behaviors. 36 …”
Section: Figurementioning
confidence: 99%
“…35 The Strengths and Difficulties Questionnaire is a local validated questionnaire assessing 5 aspects of adolescent life, including emotional problems, conduct problems, peer relationships, hyperactivity/ inattention, and prosocial behaviors. 36 …”
Section: Figurementioning
confidence: 99%
“…There are other advantages of the SDQ: it is multi-informant, some items have a positive wording, and both difficulties and strengths are covered (Goodman 1997; Goodman and Scott 1999). The validity and reliability of the SDQ has been shown in numerous studies both in western (Essau et al 2012; Gómez-Beneyto et al 2013; Koskelainen et al 2000; Marzocchi et al 2004; Obel et al 2004; Shojaei et al 2009; Smedje et al 1999; Widenfelt et al 2003) and non-western cultures (Alyahri and Goodman 2006; Lai et al 2010; Mansbach-Kleinfeld et al 2010; Samad et al 2005; Woerner et al 2004). Goodman showed that the original SDQ has an ability to discriminate between high and low risk groups similar to that of the Rutter questionnaires, while SDQ provides better coverage of inattention, peer relationship problems, and prosocial behavior (Goodman 1997).…”
Section: Introductionmentioning
confidence: 96%
“…The mean scores from this study were also compared with studies from China (Du et al, 2008), Hong Kong (Lai et al, 2010) and UK (Department of Health, Department for Education and Skills, 2004) (Table III).…”
Section: Parent-sdqmentioning
confidence: 99%
“…Both the extended English and Chinese version of the parent-SDQ were available for parents. The Chinese version of the SDQ has been validated in different studies (Du et al, 2008;Lai et al, 2010). Parents' report was used to estimate the rate of mental health and behavioural difficulties of Chinese children attending the Chinese language schools.…”
Section: Questionnairesmentioning
confidence: 99%